O2E.5 Challenges in pesticide exposure assessment for epidemiologic studies. (April 2019) - Freeman, Laura Beane
Abstract : Pesticides are used extensively worldwide to control weeds, insects and other pests, some of which have been linked to numerous adverse health outcomes, including cancer. Their ubiquity makes it imperative to conduct high quality epidemiologic studies of these chemicals for hazard identification and risk assessment. There are hundreds of pesticides and pesticide active ingredients registered for use worldwide. However, only a handful have been formally evaluated for carcinogenicity, partially due to the paucity of high quality studies with information on specific active ingredients. Some of the challenges related to assessing exposure to these chemicals are not unique, but there are some particular circumstances that make evaluation of pesticides particularly challenging. Although agricultural practices are changing in many parts of the world, pesticides have traditionally been applied on family farms or small workplaces with few employees. Many studies have relied on the self-report of pesticides; however, depending on the specific work practices, the workers applying the pesticides may not know what chemicals are being applied and may not be able to report the specific active ingredients directly. Other studies have inferred exposure to individual chemicals using a variety of methods, including individual reports of general pesticide application, the crops being grown and combining these data with auxiliary information, such as sales or registration records, application diaries or the use of local experts to assign probability of exposure. In addition to the specific active ingredient, the intensity of exposure is related to other factors, including those associated with application methods and the use of personal protective equipment. Pesticides are often applied in combination with one another, or in mixtures and applicators may apply or be exposed to multiple chemicals through a growing season. Despite these, and other challenges, high quality exposure assessment is critical to studies of these important chemicals.